A First Report of Aeromonas veronii Infection of the Sea Bass, Lateolabrax maculatus in China - Wang, Baotun; Mao, Can; Feng, Juan; Li, Yong; Hu, Jianmei; Jiang, Biao; Gu, Qunhong; Su, Youlu (Frontiers in Veterinary Science, 2021)
The sea bass, Lateolabrax maculatus is commercially farmed in Zhuhai, located in the Guangdong Province of China. L. maculatus in aquaculture have suffered acute death, characterized by ulcerations on the body surface, congestion, and hemorrhage in internal organs such as liver, kidney, and spleen. The dominant infecting strain of bacteria isolated from the kidneys of diseased fish was identified as Aeromonas veronii (strain 18BJ181). This identification was based on analysis of morphological, physiological, and biochemical features, as well as 16S rRNA and gyrB gene sequences. Drug sensitivity testing showed that the strain 18BJ181 isolate was resistant to four antibacterial drugs, including amoxicillin, madinomycin, penicillin and sulfamethoxazole, while moderately sensitive to erythromycin and rifampicin. The detection of growth characteristics showed that the strain 18BJ181 exhibited adaptability to the environment. In addition, some virulence genes, such as aer, act, gcaT, tapA and fla, were detected in the strain 18BJ181. The median lethal dosage of the strain 18BJ181 isolate in L. maculatus was 8.5×105 and 4.2×105 cfu/g under the conditions of intraperitoneal injection and intramuscular injection, respectively. The experimentally induced infection showed that the 18BJ181 isolate caused considerable histological lesions in L. maculatus, including tissue degeneration, necrosis, and different degrees of hemorrhage. These results provided evidence for a more comprehensive understanding of A. veronii strain 18BJ181 infection in L. maculatus.